Transformational leadership, personality traits and teachers' creativity: a mediating role of intrinsic motivation - Majeed, Abdul (2018)
Creativity in the education sector of Balochistan a province of Pakistan, has been reported to be poor to an alarming extent. Lack of creativity among teachers inevitably keeps a society deprived of having a workforce which has cutting-edge skills as well as high integrity. Accordingly, drawing upon the investment theory of creativity and intrinsic motivation theory, the principal objective of this research is to assess the intrinsic motivation as a mediator on the relationship between transformational leadership and its dimensions, personality and its dimensions and creativity in Quetta, Balochistan This study utilized a quantitative method, and 239 usable questionaires were gathered from the college teachers of Government colleges in Quetta, Balochistan Partial Least Squares (PLS) was utilized to analyze the data. The results reveal that transformational leadership and its dimensions viz., intellectual stimulation, individualized consideration. idealized influence and inspirational motivation have a significant positive direct relationship with creativity. Likewise, personality, openness to experience and extraversion have a direct positive significant relationship with creativity. Moreover, the relationship of conscientiousness, agreeableness, and neuroticism with college teachers' creativity is not significant. Similarly, intrinsic motivation mediates the relationship between transformational leadership and creativity, intellectual stimulation and creativity but does not mediate the relationships of individualized consideration, idealized influence, and inspirational motivation, taken with creativity. Intrinsic motivation has a mediating effect on the relationships of personality, openness to experience, conscientiousness, agreeableness, extraversion, and neuroticism, taken with teachers' creativity. Findings of this research provide an insightful understanding of the utilization of investment theory of creativity and intrinsic motivation theory in creativity research in the education sector, particularly in developing economies. The findings contribute a new knowledge by investigating the mediating strengths of internal motivation on the relationships of personality and leadership taken with creativity. Practically, this research gives important vision to the educators, policymakers, and researchers to additionally comprehend the impacts of transformational leaders and personality on the teachers' creativity.